Teknik Genogram Terhadap Keputusan Karir Mahasiswa Prodi Bimbingan Konseling Islam - Andi Zulfiana; Nurul Faizah K; Andi Nurindah Sari (Pusat Riset dan Inovasi Nasional, 2024)
The purpose of this study (1) to find out the description of the implementation of the genogram technique on the career decisions of students in Prodi BPI IAIN Bone(2) to find out the description of the career decisions of students at Prodi BPI IAIN Bone(3) to test whether the use of the genogram technique can improve the career decisions of class students at prodi BPI IAIN Bone. This research approach is a quantitative approach using a quasi experimental design with a Pretest-Posttest Control Group Design research design, on 20 samples. Data collection techniques, namely: the scale of career decisions, observation, and interviews. Data analysis used descriptive analysis of non-parametric Wilcoxon signed ranks test. Research results are (1) The description of the implementation of the genogram technique on career decisions before the administration of the genogram technique is in the low category and after the use of the genogram technique is in the high category Prodi BPI IAIN BoneCity (2) The implementation of the career decisions of students in Prodi BPI IAIN Bone increases after the use of the genogram technique . (3) The use of genogram techniques can improve student career decisions in Prodi BPI IAIN Bone.